DeFi era: the behavioral intentions toward cryptocurrency in Lebanon - Ali Abdel Karim Abou Ali (Innovation & Management Review, 2024)
Purpose - This paper examines the factors which impact the behavioral intentions toward cryptocurrency based on signaling theory. Design/methodology/approach - Data were collected through online questionnaire, and responses from 223 individuals in Lebanon were analyzed through SEM technique using Amos 24. Findings - The outcomes portrayed the positive effect of perceived benefits and trust in cryptocurrency on behavioral intentions toward cryptocurrency; while not supporting the hypothesized influence of herd behavior and regulatory support. Originality/value - This paper is among the first studies to adopt Signaling Theory (ST) in the cryptocurrency behavioral intentions research. Moreover, it is of the initial efforts in Lebanon and Middle East in evaluating behavioral intentions to use cryptocurrency, and it provide insights for future researchers, crypto project owners, crypto investors and crypto trading platforms.
Keywords: 650; Perceived benefits; Cryptocurrency; Herd behavior; Usage intentions; Regulatory support; Trust in cryptocurrency